Pengaruh Lingkungan Kerja dan Fasilitas terhadap Loyalitas Karyawan PT. Televisi Transformasi Indonesia - Suriansha, Reza (Journal of Economics & Business UBS, 2020)
The research aims to examine and analyze the influence of working environment and facility toward employee loyalty PT. Televisi Transformasi Indonesia. Data collected through distribution of questionnaires and it is implemented to PT. Televisi Transformasi Indonesia 85 employee. Analysis of data in this research using the help of SPSS version 22. The study was conducted during the period July 2017 - October 2017. Analysis technique used is multiple regression. It also tested validity test, regression analyze, and the classical assumtions that included normality test, multicollinearity test, and heteroscedasticity test. The result this research found no variables that deviate from the classical assumtions, this suggest that the available data has been qualified to use the model of multiple linear regression equation. From the results showed that the variable leadership style and motivation is partially postivie significantly. The predictive capability of the two variables on performance employee of 70,5%.